Analisis Strategi Pemasaran pada PT Tomoe Valve Batam - Golan Hasan; Ade Pratama; Intan Permata; Okta Riza; Oktaviana Oktaviana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The purpose of this article is to find out the marketing strategies implemented by PT Tomoe Valve Batam in reaching its business to various countries. As a branch in Indonesia located in Batam City, marketing is implemented efficiently and well in marketing products. International marketing has been implemented through social media platforms so that this makes it easier and increases the company's sales targets. Marketing strategy is one of the effective product introduction tactics.